1981
DOI: 10.1128/iai.31.1.480-486.1981
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella bacilliformis: colonial types and erythrocyte adherence

Abstract: Bartonella bacilliformis was cultivated on a solid medium, and two bartonella colonial morphologies were differentiated and designated colony types Ti and T2. Although both Ti and T2 bartonellae adhered to human erythrocytes in vitro, approximately twice as many T2 bartonellae adhered as did Ti. Maximum adherence required bartonella energy, most likely proton motive force-dependent motility. Bartonellae did not penetrate or lyse erythrocytes in vitro. Bartonellae adhered poorly to a-or ,8-glucosidase-treated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 11 publications
3
22
0
1
Order By: Relevance
“…Bacterial uptake must therefore be actively triggered by the pathogen. Consistently, energy depletion in bacteria impeded invasion of B. bacilliformis into erythrocytes (Walker and Winkler, ). One of likely several energy‐dependent steps in B. bacilliformis uptake into erythrocytes is the initial attachment to the erythrocyte membrane.…”
Section: Infection Of Erythrocytesmentioning
confidence: 84%
See 1 more Smart Citation
“…Bacterial uptake must therefore be actively triggered by the pathogen. Consistently, energy depletion in bacteria impeded invasion of B. bacilliformis into erythrocytes (Walker and Winkler, ). One of likely several energy‐dependent steps in B. bacilliformis uptake into erythrocytes is the initial attachment to the erythrocyte membrane.…”
Section: Infection Of Erythrocytesmentioning
confidence: 84%
“…Indeed, a block of flagella by antibodies diminishes the association with erythrocytes (Scherer et al ., ). Non‐motile B. bacilliformis do not attach to erythrocytes at all (Walker and Winkler, ), yet flagella isolated from B. bacilliformis do not bind to erythrocytes. The role of flagella in erythrocytic adherence thus remains controversial.…”
Section: Infection Of Erythrocytesmentioning
confidence: 99%
“…infection in their reservoir hosts, but not in the incidental hosts, is a longlasting intraerythrocytic bacteremia. This also applies to the human-specific B. quintana (Rolain et al, 2002;Rolain et al, 2003c), a louse-transmitted bacterium that was initially detected during World War I as the causative agent of trench fever (5-day fever), and B. bacilliformis (Walker & Winkler, 1981;Benson et al, 1986), a sand fly-transmitted bacterium (Maguiña et al, 2009). Bartonella bacilliformis is so far the only known species of Bartonella spp.…”
Section: Adhesion To the Erythrocytesmentioning
confidence: 99%
“…Some characterization of erythrocyte receptors and bartonella ligands has been attempted, yielding somewhat conflicting results, although there does appear to be a carbohydrate component to the receptor. 29 Molecular studies have identified two genetic loci that encode proteins that appear to have a role in erythrocyte association. The first of these loci, the ial locus, comprising two genes ialA and ialB, was identified by its ability to confer an erythrocyte-invading phenotype on E. coli cells into which it had been introduced.…”
Section: Exploitation Of Erythrocytesmentioning
confidence: 99%